Gender Gap Evolution in Europe During the Great Recession: an Institutionalist Approach - Carole Brunet; Esther Jeffers (Revue de la Régulation)
This paper examines the evolution of labor market gender gaps during the Great Recession in Europe. We focus on participation, employment, part-time, and unemployment gender gaps, and estimate fixed effects models that incorporate social, economic and institutional features of 14 European Union member states from 2003 to 2013. Our results indicate that gender gaps decreased during that time span, particularly during the recession years. Economic growth seems to foster gender inequalities, while more employment in the service sector or in the public sector tends to lower gender gaps. Labor market institutions, such as unionization and minimum wage policies, as well as employment protection for regular contracts, tend to narrow employment inequalities between female and male workers, whereas product market regulation increases gender gaps in participation and employment.